Antibodies against C1q in anti-glomerular basement membrane nephritis. - Coremans, I E (1992)
The prevalence of antibodies against the collagen-like region of the subcomponent of the first component of complement, C1q, was investigated in 11 patients with anti-glomerular basement membrane (GBM) nephritis. Anti-C1q antibodies (anti-C1qAb) were detected in seven patients. IgG anti-C1qAb were found in four and IgA anti-C1qAb in five patients. During follow up of the patients a relationship was observed between the levels of IgG anti-C1qAb and the levels of anti-GBM antibodies (anti-GBMAb). Gelfiltration experiments indicated that both IgG anti-C1qAb as well as IgG anti-GBMAb were monomeric and that binding also occurred with the F(ab')2 fragments of the antibodies. Although anti-C1qAb and anti-GBMAb are both directed against a collagen-like structure, it was demonstrated by means of inhibition experiments that anti-C1qAb and anti-GBMAb are directed against different antigenic sites. Comparison of patients with anti-GBM nephritis with and without anti-C1qAb revealed that there were no differences in disease activity or disease severity. Therefore, the results of this study suggest that anti-C1qAb do not play a direct pathogenetic role in anti-GBM nephritis.